Perlindungan Hukum Bagi Importir Tanaman Hias Online Dalam Melakukan Transaksi Ekspor-Impor Terhadap Wanprestasi Eksportir - Sihite, Sri Rumada (Fakultas Hukum Universitas Pattimura, 2023)
Introduction: Ornamental plants come from various countries, both within and outside our country, Indonesia. One of them is Bangkok. Ornamental plants or often also called flowers, especially ornamental plants from Bangkok, which has a flower market, also have a lot of interest in our country, Indonesia. Transactions between exporters and importers of ornamental plants experience problems and have problems.Purposes of the Research: Know and understand the problems of exporting and importing ornamental plants.Methods of the Research: This research is normative research using a statutory approach with the sources of legal materials used are primary legal materials and secondary legal materials and tertiary legal materials with qualitative analysis.Results of the Research: The problem in the title is what legal protection is provided by the importer of ornamental plants if there is an importer's default such as the ornamental plant wilting and within a few days after being replanted the ornamental plant must be thrown away and cannot be resold. Refers to the obligations of the seller and buyer based on Article 1474 of the Civil Code, which states that the seller has the obligation to hand over the object and what he is selling and assume or guarantee it.